Problemy w nauczaniu języka hiszpańskiego o charakterze biznesowym na poziomie podstawowym w kontekście ekspansji niektórych przedsiębiorstw na Dolnym Śląsku - Kubacki, Tomasz (Problems in Teaching Basic Business Spanish in the Context of the Expansion of Some Enterprises in the Lower Silesia Region, 2008)
Typical problems of foreign language teaching, especially those that apply to study of languages for special purposes (business, economics), are especially vivid in relation to Spanish - an increasingly popular, but still fairly under-represented language of choice for Polish students. This is manifested in relatively small number of students at intermediate and advanced level, compared to a huge representation of elementary level students. In the light of the above, special attention should be given not only to the scope and methods of teaching, but also ways of introducing special-purpose language needed in business training, related to professional ambitions of both students and lecturers concerned with fitness of language training to profile of the studies. Of great importance here is also the process of gradual limitation of didactic resources directed to language teaching, as well as the need to unify training programs. The near future will inevitably bring the necessity for efficient and rapid acquisition of a foreign language of choice, paired with handicap in providing individual and group training to suit the students' needs (especially the support for 'over- and under-achievers'). Consequently, teaching of foreign business language at elementary level may prove extremely hard. Another concern is the tendency for local companies to employ graduates of humanistic sciences for business positions. This phenomenon, if wide-spread, may lead to considerable changes on local labour market. Thus, it seems necessary for education authorities to devise ways to monitor this issue, and for the teachers of foreign languages to address this issue in preparation of curricula and in everyday teaching practice.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 209-215